Saudi-Qatari relations during the period 1990-2003 and Their Point of View Against the Conflicts in Gulf Region - Al-Jazi, Mohammad Abdul-Hadi Saleh; Al-Jazi, Anwar Debbshi (Journal of History Culture and Art Research, 2020)
This study comes to cover the Saudi-Qatari relations during the period (1990-2003) and the events and attitudes that took place both at the regional and global levels, and their position on it. This study came to start a period of decisive measures to demarcate the borders between the two countries and the security breach between the two countries on the border post in Al-Khfous border in 1992. This study also came to show what took place in negotiations and from international mediations to solve the problems once and for all. The study also came to clarify the position of Saudi Arabia and Qatar regarding the Iraqi invasion in 1990 against Kuwait and the second Gulf war, the issue of Gulf security (national security - oil), and international and regional alliances to reduce this threat. This study clarifies the position of Saudi mediation to end the Qatari and Bahraini dispute over the "Hawar Islands", and discusses if the mediation have an effective role in ending the dispute between Qatar and Bahrain or not?